GEOS-Chem Code v11-01 - Silva, Sam (Zenodo, 2020)
This is the GEOS-Chem Code used in Silva et al. (Submitted), "Exploring the Constraints on Simulated Aerosol Sources and Transport across the North Atlantic with Island-Based Sun Photometers"